Workshop Pemanfaatan Brand Dan Sosial Media Untuk Pemasaran Digital Desa Matansala Kabupaten Morowali - Moh. Zeylo Auriza; Muh. Isra Iradat (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2026)
Intan Permata MSME, located in Matansala Village, Bungku Tengah District, Morowali Regency, is a micro-business engaged in ecoprint production with the aim of empowering the community, especially housewives and young people, through sustainable entrepreneurship activities. This MSME faces major obstacles in digital marketing, which has resulted in low competitiveness and limited market reach. The urgency of this problem lies in the importance of optimising the brand and social media as effective promotional tools to increase the reach of ecoprint products. This study aims to identify the digital marketing obstacles faced by Intan Permata MSME and to design a more effective social media-based marketing strategy. The methods used in this study include qualitative and quantitative approaches, with data collection techniques through observation, interviews, and analysis of SME social media. In addition, training and mentoring will be provided to business actors to improve their understanding and skills in digital marketing. The targeted outcomes of this research include improved digital marketing skills for MSME entrepreneurs, more effective social media-based marketing strategies, and increased engagement and sales of ecoprint products through digital platforms..